Survey and Trend of Some Zoometric Parameters Correlated to the Growth of Male Subjects of Mediterranean Italian Buffalo for Meat Production - Coletta, A.; Di Rubbo, M.; Caso, C.; Fez, C.; Rossi, N.; Vittoria, R. (Journal of Buffalo Science, 2012)
In this study was evaluated the presence of hereditary disposition to meat production in Mediterranean Italian buffaloes through the analysis of variation of certain important parameters related to the production of meat, in 40 young subjects having the same age. The parameters studied were: live weight, daily weight gain (DWG), withers height, thoracic circumference and trunk length. These values were investigated by controls every 21 days during the period of major growth of the animals, that is from the 240th day of life up to the attainment of slaughter weight. This work has pointed out that there are significant differences in growth between animals of the same age. The data suggested that hasn’t yet been made any selection about the presence of hereditary disposition to meat production in Mediterranean Italian Buffalo.